P-195 Collaborative working between children and adult palliative care/hospice services. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Smith, Louise; Longford, Emma; Curtis, Andy
Abstract : Background: It is well documented that transition is a scary, isolating process for young persons (YPs) and their families, with clear gaps in services (Care Quality Commission, 2014). Claire House collaborated with Wirral Hospice for an individual patient and positive outcomes were reported. We aim to replicate this offer to all YPs, offering a coordinated, continuous collaboration and opportunity to build relationships safely. Aim: To provide a collaborative service for all YPs, comprising a five-year overlap of services. To manage palliative care needs jointly, improve symptom management and quality of life. This collaboration will provide opportunity for adult services to extend knowledge of previously childhood conditions (Care Quality Commission, 2014). Method: Families were invited to joint presentation evenings facilitating early relationship building and allowing exploration of what is wanted (NICE, 2016; Chambers, 2015). Agreed to offer joint clinics (Chambers, 2015), parallel planning discussions, symptom management, and social events to enable YPs to build relationships. Expected results: Increased quality of life for YPs, improved symptom management, fewer hospital admissions, more support for families (both peer and professional), greater opportunity to build sustainable relations. The team will seek purposeful feedback at regular YP sessions, and professional feedback. Conclusions: This project will provide a choice of services offering support to YPs and their families throughout transition and providing a continuous, collaborative relationship with SPC services. It will enable adult services to gain the right skills to meet the complex needs of increasingly dependent YPs. Innovative/of interest: Children are living longer, increasing the need for access to adult palliative care. There exists a gap in knowledge of adult services, for previously exclusive childhood diseases and inequitable service provision. This project will enable children's hospices and adult palliative care services to work together and improve the struggle that families and YPs face with transition and relationship-building with adult services.